Les principes que la Grèce ignorait. Rosenzweig and Levinas on Language, Ethics and Jewish Heritage - Fonti, Diego Osvaldo (2014)
The purpose of this paper is to show how Franz Rosenzweig and Emmanuel Levinas offer an answer to the relationship between particularity and universality by resorting to their own Jewish heritage. Both philosophers begin with a hermeneutics of communication, a philosophy of language based on the facticity of language. But this hermeneutics is dependent upon a horizon of understanding inherited from the Jewish tradition. This includes a kind of responsibility for the other and a kind of heteronomy that enriches the modern concept of autonomy. Finally they find in every genuine communication a prophetic element.